1992
DOI: 10.1007/bf00146884
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for breast cancer by age and menopausal status: a case-control study in Singapore

Abstract: A case-control study was conducted among Singapore Chinese women, comprised of 200 histologically confirmed cases of breast cancer and 420 hospital controls. Subjects were interviewed on family history of breast cancer, social and demographic characteristics, reproductive history, and diet one year prior to interview. Differences in risk factors were observed according to menopausal status. In the premenopausal group, the most consistently significant nondietary effect was an increased risk with late age at fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
79
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 20 publications
(10 reference statements)
10
79
2
Order By: Relevance
“…Alternatively this possible emergence of an association in a recent study in China could be due to greater variability in soy consumption in recent years as more people adopt a less traditional diet, with some reducing their soy intake below a threshold level needed to provide protection against breast cancer. This hypothesis is consistent with results from studies of Asians living in the United States, 48,49 and of Chinese in Singapore, 50,51 where a mixture of traditional and western diets predominates, that showed evidence for a protective effect of soy against breast cancer. The results of our study are also supportive of this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…Alternatively this possible emergence of an association in a recent study in China could be due to greater variability in soy consumption in recent years as more people adopt a less traditional diet, with some reducing their soy intake below a threshold level needed to provide protection against breast cancer. This hypothesis is consistent with results from studies of Asians living in the United States, 48,49 and of Chinese in Singapore, 50,51 where a mixture of traditional and western diets predominates, that showed evidence for a protective effect of soy against breast cancer. The results of our study are also supportive of this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…45,46 Two early studies found evidence for a protective effect of soy food intake in premenopausal but not among postmenopausal women. 29,47 However, findings from other studies of isoflavone intake in pre-and postmenopausal women separately have been inconsistent, 9,10,12,43,44,48 with most reporting no significant association, as was found in the current study. Since HRT use may mask or alter any association of isoflavone intake with breast cancer risk, we repeated the analysis for women who were not using HRT, but still observed no significant relationship between isoflavone intake and risk for breast cancer.…”
Section: Main Findingscontrasting
confidence: 62%
“…Two early case-control studies in predominantly Asian populations suggested that a high intake of soy food may be protective against breast cancer in women. 29,30 Since plasma concentrations of isoflavones in postmenopausal women who consume soy foods are up to 1,000 times higher than those of oestradiol, and phytoestrogens are structurally similar to endogenous oestrogens, it has been suggested that such an association This factor is unknown for some women-these ''unknowns'' are excluded from the calculations of percentages. may exist because isoflavones may have an anti-oestrogenic effect.…”
Section: Main Findingsmentioning
confidence: 99%
“…The reasons for this are not clear, but the proximity of younger women to the aetiologically relevant time period is a possible explanation. Several previous studies have considered differences by menopausal status in the effect of micronutrients (La Vecchia et al, 1987;Katsouyanni et al, 1988;Marubini et al, 1988;Rohan et al, 1988;Howe et al, 1990;Richardson et al, 1991;Zaridze et al, 1991;Lee et al, 1992;Hunter et al, 1993;Rohan et al, 1993;Yuan et al, 1995), but with inconsistent results. Approximately half of all studies reporting results by menopausal status indicate no differences in pre-and postmenopausal women (La Vecchia et al, 1987;Katsouyanni et al, 1988;Marubini et al, 1988;Rohan et al, 1993;Yuan et al, 1995).…”
Section: Discussionmentioning
confidence: 99%